Regional studies : the interplay of land and people - Lich, Glen E., 1948- (College Station, Tex. : Texas A & M University Press, 1992)
What makes a region a region, and how does one region differ from another? What are the tests of evidence of regionalism? What boundaries have meaning--political, geophysical, economic, cultural, psychological, ethnic, linguistic? Are there special problems in reporting findings about life within a region? These questions and others regarding methods and interdisciplinary content run through this stimulating series of papers on the interplay of land and people. While the.
Concept of region means different things to different academic disciplines, the contributors to this volume agree that the study of regions and regionalism can--and should--be undertaken with seriousness. Contributors include William R. Ferris, Terry G. Jordan, Howard R. Lamar, Ann R. Markusen, Charles Hamm, Samuel S. Hill, Susan H. Armitage, Frederic G. Cassidy, Wilbur Zelinsky, Oscar J. Martinez, and Lynwood Montell. Glen E. Lich, the volume's editor, provides a.
Concluding overview. The volume is arranged in three parts. The opening section addresses the comparative study of regions, and the second section applies multidisciplinary considerations to the study of regionalism and economics, politics, culture, religion, gender, and language. The last section points toward four closely connected issues: the definition and use of variables in regionalism, approaches to regions both large and small, and a final appeal for integrative.
And comparative perspectives. This volume places the study of regionalism within the wide parameters of the history of the concept, its significance in western thought, and its many and varied manifestations.
Region as art / William R. Ferris -- The concept and method / Terry G. Jordan -- Regionalism and the broad methodological problem / Howard R. Lamar -- The economics and politics of regionalism / Ann R. Markusen -- The media, politics, and regionalism / Charles Hamm -- Region and religion / Samuel S. Hill -- Gender and regionalism / Susan H. Armitage -- The language of regionalism / Frederic G. Cassidy -- The changing character of North American culture areas / Wilbur Zelinsky -- A binational region : the borderlands / Oscar J. Martínez -- A subregion : the Upper Cumberland / Lynwood Montell -- Spatial integration : the argument for context / Glen E. Lich.
Based on papers from a symposium held at Baylor University in 1987.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Texas -- Civilization -- 20th century -- Congresses; Regionalism -- Texas -- Congresses; Human geography -- Texas -- Congresses; Texas -- Rural conditions -- Congresses; Regionalism -- Texas -- Congresses; Cultural geography -- Texas -- Congresses; Texas -- Civilization -- 20th century -- Congresses; Texas -- Rural conditions -- Congresses; Régionalisme -- Texas -- Congrès.; Géographie culturelle -- Texas -- Congrès.; Texas -- Civilisation -- 20e siècle -- Congrès.; Texas -- Conditions rurales -- Congrès.; Texas -- Civilisation -- 20e siècle -- Congrès.; Régionalisme -- Texas -- Congrès.; Texas -- Conditions rurales -- Congrès.; HISTORY -- State & Local -- General; Cultural geography; Civilization; Human geography; Regionalism; Rural conditions; Texas; Régionalisme -- Congrès.; Géographie humaine -- Congrès.; Régions administratives -- Amérique du Nord -- Congrès.; 1900-1999; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.